Portaria PGR/MPF nº 861, de 7 de outubro de 2020 - Antonio Augusto Brandao de Aras (DOU, Brasília, DF, 9 out. 2020. Seção 2, p. 47., 2020)
Revoga, a pedido, a Portaria PGR/MPF nº 108, de 16 de fevereiro de 2018.